Customer Relationship Management Strategies in Coffee Shops: A Literature-Based Analysis of Kopi Kenangan - Tamara Indhira, Sekar; Lubis, Muharman; Wirawan, Muhammad Naufal; Tiara Citra Maharany, Sekar; Fauzan, Ratandi (Yayasan Asmin Intelektual Berkah, 2026)
This study presents a literature-based analysis of Customer Relationship Management (CRM) strategies in coffee shops, with a particular focus on Kopi Kenangan as a prominent coffee chain in Indonesia. The study aims to identify how CRM practices are reflected in both physical store experience and digital customer engagement through the brand’s mobile application, and to examine how these practices may relate to customer satisfaction and loyalty. The research employed a descriptive qualitative literature review by analyzing scholarly journal articles, conference proceedings, and relevant secondary reports. The reviewed literature suggests that integrated CRM practices in coffee shops commonly operate through two complementary channels: in-store relationship building and digital relationship management. In-store factors such as servicescape, service quality, and customer-friendly facilities are consistently associated with positive customer experiences, while digital features such as mobile ordering, loyalty mechanisms, and promotional communication may enhance convenience, engagement, and repeat purchase intention. In the context of Kopi Kenangan, the available literature indicates that the combination of offline and online CRM strategies is likely to support customer relationship development and brand loyalty. This study concludes that the integration of service experience and digital engagement represents an important CRM approach in the contemporary coffee shop industry, while also highlighting the need for future empirical studies to validate these patterns more directly.